Pumpkinseed population characteristics in a Northeast South Dakota glacial Lake - Jeston D. Hassler; Brian G. Blackwell; Todd M. Kaufman (Journal of Freshwater Ecology)
Eastern South Dakota represents the western extent of the Pumpkinseed Lepomis gibbosus native range. Lake Enemy Swim, just to the west of the native range, has the highest Pumpkinseed abundance in this region. Information about the Pumpkinseed population characteristics in Lake Enemy Swim could aid in managing the species. Our study objectives were to 1) describe current Pumpkinseed population characteristics in Lake Enemy Swim and 2) examine if they have changed over the last 25 years. We collected Pumpkinseeds in May 2023 with modified-fyke nets and angling and during annual population sampling with modified-fyke nets from 1999–2023. The Lake Enemy Swim Pumpkinseed population is not abundant and has persisted at a low level from 1999–2023. Population size structure was variable but generally trended downward since the early 2000s. In 2023, the maximum estimated age was 8 years, growth was average, with fish attaining 150 mm at age 4, and the von Bertalanffy growth model predicted an asymptotic length of 205 mm. However, since 2015, no fish exceeding 200 mm have been observed. Yearly relative weight (Wr) means generally exceeded 95. In 2023, annual mortality was estimated at 29%, and recent recruitment appears consistent but low magnitude. The Pumpkinseed sport fishery in Lake Enemy Swim is limited due to the low population abundance and small size structure. The recent invasion of Zebra Mussels Dreissena polymorpha may provide a new food source, which could lead to improved growth and size structure. This study provides baseline information concerning a Pumpkinseed population near the western extent of their native range now subjected to Zebra Mussel infestation.